2000
DOI: 10.1034/j.1399-3003.2000.16d13.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal lipid peroxidation in patients with sleep apnoea

Abstract: The prevalence of cardiovascular diseases is increased in patients with the obstructive sleep apnoea syndrome (OSAS). The fall and rise of arterial oxygenation that follows each apnoea may increase lipid peroxidation and contributes to explaining this association. In the present study, the authors determined lipid peroxidation in patients with OSAS and the effect of treatment with continuous positive airway pressure (CPAP).Fourteen male patients with severe OSAS (59 5 apnoea . h -1 ) ( SEM) and 13 healthy nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
115
1
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(131 citation statements)
references
References 23 publications
8
115
1
7
Order By: Relevance
“…Barcelo et al [26] also reported that the lipid peroxidation profile is abnormal in OSA patients. Using LDL particles isolated from 14 patients with severe OSA (59 apnea/h) and 13 healthy subjects, they found that thiobarbituric acid-reactive substance (TBARS) formation was higher in OSA patients.…”
Section: Evidence For Oxidative Stress In Osa Patientsmentioning
confidence: 96%
“…Barcelo et al [26] also reported that the lipid peroxidation profile is abnormal in OSA patients. Using LDL particles isolated from 14 patients with severe OSA (59 apnea/h) and 13 healthy subjects, they found that thiobarbituric acid-reactive substance (TBARS) formation was higher in OSA patients.…”
Section: Evidence For Oxidative Stress In Osa Patientsmentioning
confidence: 96%
“…In particular, obese individuals with systemic hypoxemia (because of sleep-related breathing disorders including obstructive sleep apnea) may experience repeated bouts of hepatic hypoxia, hepatocyte necrosis, and ultimately develop NASH. Several pieces of evidence support the possibility that hypoxemia may play a role in pathogenesis of NASH: First, sleep disturbances and nocturnal hypoxemia are common in patients with NASH (Table 2); second, hypoxemia has been shown to alter the activity of different CYPs 27,28 ; third, sleep apnea and hypoxemia have been associated with lipid peroxidation and oxidative stress 29 ; and, fourth, in the dietary model of animal NASH 6 as well as the human study by Weltman et al, 8 CYP2E1 activity was most prominent in zone III, the least oxygenated area of the acinus. The significant association noted in this study between hepatic CYP2E1 activity and nocturnal hypoxemia is interesting.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, OSAHS has been found to be a factor involved in endothelial dysfunction, 11 infl ammation, 12 and sympathetic activation, which may promote ischemic events. Although an increased incidence of CAD has been found in patients with OSAHS, 13,14 and even mild to moderate OSAHS has been associated with a worse prognosis in patients with existing CAD, 15,16 the characterization of OSAHS in the acute myocardial ischemia setting is less clear. [17][18][19][20][21][22][23][24][25] Based on the results of recent studies 19,20,25 it is diffi cult to determine whether OSAHS contributes to the occurrence of ACS, or whether OSAHS is a consequence of the acute phase in ACS patients that may improve after medical stabilisation.…”
mentioning
confidence: 99%